Critical Discourse Analysis (CDA) on Qualitative Research : A Review - Rika Armayanti (REiLA : Journal of Research and Innovation in Language, 2019)
This article discusses critical discourse theory as a qualitative research theory. Analytical frameworks include analysis of texts, communication and social practices in local, corporate and social levels. It has the goal of expressing and engaging in politics to discuss or deal with certain research methods, statements or values. It refers to the need to explain, understand, analyze, and criticize social life that reflects in text using critical discourse analysis. According to Lake (1996), “The authors use texts to understand their world and at the same time, the article admits to creating actions and social relationships in everyday life, while text positions and individual buildings provide different meanings, ideas, and world versions”.